Synthesis, Spectroscopic and Biological Studies of Some Metal Complexes with 2,2-Diamino–N–Phenyl Hydrazo Benzene - Naji, Shaymaa H; Jabir, Majid S; Musa, Falih H (Al-Nahrain Journal of Science, 2018)
The ligand of 2,2`diamino–N–phenyl hydrazo benzene (L) has been prepared from the reaction of ortho amino hydrazo benzene with ortho amino phenyl thiol in mole ratio1:1and characterized by elemental analysis (C, H, N), IR, UV-Vis. The complexes of bivalent (Co, Ni, Cu, Zn, Pd, Cd, Hg and Pb)ions and trivalent (Cr)ion have been prepared and characterized too. The structural diagnosis were established by IR, UV-Visible spectrum, Conductivities, atomic absorption and magnetic susceptibility. The complexes showed octahedral geometry around the metal ion with the (N,N,N) ligand coordinated in tridentate mode except pd complex showed trigonal bibyramidal. , kf, Єmax for the complexes were estimated too.  for Co – complex was calculated. The study of biological activity of the ligand (L) and its complexes showed various activity toward Streptococcus pyogenes, Staphylococcus aureus, E. coli, Pseudomonas aeruginosa and Candida albicans.